2007
DOI: 10.1159/000107286
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide and TNFα Effects in Experimental Autoimmune Encephalomyelitis Demyelination

Abstract: The involvement of inducible nitric oxide synthase (iNOS), which plays various roles in the progression of autoimmune diseases, was studied in iNOS knockout (KO) mice and wild-type (WT) controls with respect to experimental autoimmune encephalomyelitis (EAE). The iNOS (KO) mice presented a less severe form of the disease than the WT control mice. Although the levels of TNFα decreased in the periphery in both groups, an increase in the number of TNFα-positive cells was detected in the central nervous system dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 44 publications
0
29
0
1
Order By: Relevance
“…Production of NO, which exerts deleterious effect in EAE and MS (36,37), and MHC II surface expression, which is FIGURE 7. Liposome-encapsulated prednisolone reduces the expression of proinflammatory cytokines and chemokines, but increases M2-associated genes in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Production of NO, which exerts deleterious effect in EAE and MS (36,37), and MHC II surface expression, which is FIGURE 7. Liposome-encapsulated prednisolone reduces the expression of proinflammatory cytokines and chemokines, but increases M2-associated genes in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that pharmacological inhibitors or targeted gene deletion of iNOS and gp91phox are protective against reactive microglia-induced toxicity to neurons and OLs in culture (Xie et al, 2002;Li et al, 2005). Although a number of studies have shown that deletion of iNOS potentiates the disease severity of EAE (Fenyk-Melody et al, 1998;Sahrbacher et al, 1998;van der Veen et al, 2000van der Veen et al, , 2004Hultqvist et al, 2004;Farias et al, 2007), the contribution of NADPH oxidase in the pathogenesis of EAE has not been well elucidated. It has been reported that targeted gene deletion of p47phox can either increase or decrease the severity of several autoimmune diseases (van der Veen et al, 2000(van der Veen et al, , 2004Hultqvist et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…During the acute phase of experimental autoimmune encephalomyelitis (EAE) in mice, an increase in the number of tumor necrosis factor (TNF)-␣ -positive cells is detected in the central nervous system (CNS) [1] . The tissue-specifically expressed TNF receptors 1 and 2 (TNF-R1, TNFRSF1A; TNF-R2, TNFRSF1B) mediate apoptosis or inflammation [2] .…”
Section: Introductionmentioning
confidence: 99%